Connection between cytokines and complications derived from preeclampsia pregnancies - Pejkovska Ilieva, Maja (ScopeMed Publishing, 2020)
Preeclampsia is a condition of multiorgan involvement that can cause severe complications for the mother’s health and endanger the intrauterine development of the fetus. Purpose: The purpose is to detect the risk of developing preeclampsia in the second trimester, by examining cytokines and closely monitoring the pregnancy for complications from preeclampsia, whether they are affected by the same cytokines. Material and methods A total of 100 patients were monitored in the second trimester between 14 and 20 weeks of gestation. Values of immune biomarkers of their serum were analyzed after obtaining anamnestic data and performing ultrasound examination. With the help of the ELISA methodology, cytokines were verified: TNF-a, IL-1a, IL-2, and IL-6 versus IL-4 and IL-10. Results Of the 100 patients examined, 21 patients developed clinical symptoms and were diagnosed with preeclampsia in the third trimester. The interaction of proinflammatory interleukins is in favour of a mutual increase, and a decrease in the values of antiinflammatory interleukins is a significant predictive parameter in the second trimester for the development of preeclampsia. The increase in IL-6 is the largest statistically significant variable in the prediction of preeclampsia. The correlation between IL-6 and pregnancy complications is also with statistical significance (p=0.012). Conclusion The impaired immune response can result in consequences such as multiple organic disorders that occur in the clinical preeclampsia syndrome and problems with fetal development. The benefit of analyzing cytokines is highly significant for early diagnose and prevention of further complications.
Keywords: preeclampsia; cytokines; prediction; complications